Representasi Budaya Indonesia dalam buku Bahasa Indonesia bagi penutur asing - Kosasih, Liana; Saragih, Amrin; Sibarani, Berlin (Fakultas Sastra, 2023)
The increased interests of foreign speakers learning Indonesian language and textbook writers developing language textbook has driven studies about Indonesian cultural representation in the textbooks of Indonesian as a foreign language (BIPA). One of the cultural representations in language books is a note about the culture of the people of the target language. This study explores aspects of Indonesian culture represented in the cultural notes in an Indonesian language textbook for foreign speakers using the culture framework of Moran (2001), Yuen (2011) and Nomnian (2013). The data in this study are 22 texts of cultural notes from 'Learning Conversational Indonesian - Indonesian for Beginners' textbook. The findings showed that the Indonesian culture dimensions presented in English in the cultural notes were practices (44.9%), products (30.1%), perspectives (11.2%), people (5.1%), places (4.6%) and communities (4.1%). The findings are beneficial to reflect on what potential cultural aspects to be integrated in Indonesian language textbook for foreigners,